The Role of Coal in the International Energy Trade - F. Yu. Filimonov (Vestnik MGIMO-Universiteta, 2020)
Review of the second edition of the book by Lars Schernikau. Economics of the International Coal Trade: Why Coal Continues to Power the World. Springer, 2016. 497 p.